MANAJEMEN PUBLIK KANTOR DESA PAMARUNAN DALAM MEMBERIKAN PELAYANAN SATU ATAP KEPADA MASYARAKAT (STUDI DI KANTOR DESA PAMARUNAN, KECAMATAN KAHAYAN TENGAH, KABUPATEN PULANG PISAU) - Rara Karlina (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Palangka Raya, 2020)
The Village Office is one of the places where government tasks take place from the village head and all staff in carrying out administrative activities or activities, namely in the form of work units consisting of complete infrastructure, rooms and jobs to provide services to the community. The research method used is descriptive qualitative method that seeks to describe a social phenomenon naturally which aims to describe the nature of something that is going on in solving problems and data collection techniques by means of observation, interviews and documentation so that the data obtained is arranged systematically. The data analysis technique in this study uses data analysis according to Miles and Huberman.           The results showed that public management in the provision of services at the Pamarunan Village Office was still not optimal. This is because the office has been damaged so it needs the construction of a new office, facilities for office infrastructure are still very minimal, service time is only open until 12 o'clock and also human resources still need to increase capacity. From this, the Pamarunan Village Office is expected to continue to make improvements, both in improving facilities and infrastructure as well as evaluating human resources to continue to improve good services and work in accordance with the established standard of service operations. So that people who receive services can feel satisfied with the service provided by their village equipment. Especially for people who need a one-stop service in this village office to be more optimal to help meet the needs of the village community. Factors supporting public management at the Pamarunan Village Office in providing one-stop services are cooperation between village officials as service providers to provide maximum service, responsiveness from each village apparatus to respond to all community needs and complaints and community awareness especially communities in Pamarunan Village to follow procedures predetermined service. The inhibiting factor of public management at the Pamarunan Village Office was the lack of facilities and infrastructure because only facilities such as one-unit laptops, one-unit computers and printer were printed. This resulted in services being constrained by the incomplete facilities owned by the village office, lack of ability village officials, service time is only open until 12 noon and lacks human resources.  Keywords: Public Management, One-Stop Services, Village Communities